Melhoramento do feijão-comum para resistência a bacterioses assistido por marcadores moleculares - Coêlho, Laysla Morais (2022)
The common bean crop (Phaseolus vulgaris L.) production can be affected by several diseases, with emphasis on bacteriosis, an important focus of breeding programs once the use of resistant cultivars is the safest, most economical and most efficient control measure. Among the bacterial diseases that affect the crop, in Brazil, the common bacterial blight (CBB), widespread disease in the country, incited by bacteria, Xanthomonas phaseoli pv. phaseoli and Xanthomonas citri pv. fuscans; and the halo blight of common bean, an emerging disease of great risk to national agriculture, incited by the Pseudomonas savastanoi pv. phaseolicola (Psp). The objectives of this work were: (i) To develop halo blight resistant common bean progenies of the carioca commercial class individually containing the Pse-2 and Pse-6 resistance alleles, with the aid of marker assisted selection (MAS); (ii) To evaluate and validate the SNP snpPV0039, associated with the CBB resistance QTL-SU91 in a diverse panel of common bean parents and in an F2 population derived from the line CB911921 (QTL-SU91). In the first study, backcrosses were carried out using the sources of resistance to halo blight, ZAA-12 (Pse- 2) and BelNeb-RR1 (Pse-6) as donor parents and the carioca cultivar BRS Estilo as the recurrent parent. F1 plants were identified by genotyping with SSR markers and used as donor parents in the following backcrosses, until the F1BC3 generation. At each backcross cycle, plants were genotyped with 24 SSR markers. The genetic similarity of the BCnF1 plants with the recurrent parent BRS Estilo was estimated with the help of the Genes Program and selected the most similar plants in each BC cycle. The assisted selection of resistance alleles was monitored in BC2F1, BC3F1 and BC3F2 generations and only plants with positive results for the presence of Pse-2 and Pse-6 alleles were advanced to the next generations. For the BC3F2:3 generation, a progeny test was performed to select plants in homozygosity for the resistance loci. For each population, two BC3F2:3 common bean progenies of the carioca type were obtained, almost isogenic to the cultivar BRS Estilo (100% genetic similarity based on 24 SSR molecular markers) and also containing individually, in homozygosity, the alleles of resistance Pse-2 and Pse-6. For the second study, the genotyping of 376 elite common bean parents was carried out by the company Intertek Agritech, from the portfolio provided by the High Through-Put Genotyping (HTPG) project of molecular markers associated with different characters in beans, the marker was selected snpPV0039, which is directly associated with the QTLSU91 allele that confers resistance to CBB.To validate the marker snpPV0039, an F2 segregating population was used, derived from the cross between the CB 911921 line (QTLSU91) and a line susceptible to CBB (Genitor 1), already available among the working populations of the Embrapa breeding program. Data from Xap phenotyping and genotyping with marker snpPV0039 in the F2 generation were submitted to the chi-square test (χ2) with the aid of the R software. Among 218 F2 plants phenotyped for Xap reaction, 159 of them were characterized as resistant and 59 as susceptible, showing conformity to the expected ratio of 3R-:1rr (χ2 = 0.49; p = 0.48). snpPV0039 adhered to the ratio of 1RR:2Rr:1rr (χ2 = 1.5; p = 0.47), segregating as expected for codominant markers. Regarding the gene linkage analysis, the marker snpPV0039 used in the genotyping of the F2 population (Parent 1 x CB 911921) is linked to the QTLSU91 allele, with a recombination fraction of approximately 0.1 (10 cM). The snpPV0039 marker showed a selection efficiency of 96%, in the identification of plants with the CBB resistance allele QTLSU91 present in CB 911921, evidencing its strong linkage disequilibrium. Thus, this marker is recommended for use as a tool in the routine selection of BCC resistant genotypes in a common bean breeding program.